2012
DOI: 10.1007/s00404-012-2559-0
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected malignancies after laparoscopic-assisted supracervical hysterectomies (LASH): an analysis of 1,584 LASH cases

Abstract: The study shows that there is a small probability of unexpected malignancies even in correctly pre-screened patients for LASH procedures. Yet in the short-term (28-52 months), malign patients remain recurrence free after treatment. LASH is therefore a good procedure for assumed benign disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 35 publications
4
44
1
1
Order By: Relevance
“…Previous studies have suggested that morcellator-related dissemination of occult LMS may worsen patient prognosis, increase odds of tumor recurrence, and increase mortality [45]. Oduyebo et al [44] also suggested that patients may require surgical re-exploration and/or chemotherapy that may have been unnecessary if the uterine corpus had been Table 1) plus costs of days of disability and time lost at work.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have suggested that morcellator-related dissemination of occult LMS may worsen patient prognosis, increase odds of tumor recurrence, and increase mortality [45]. Oduyebo et al [44] also suggested that patients may require surgical re-exploration and/or chemotherapy that may have been unnecessary if the uterine corpus had been Table 1) plus costs of days of disability and time lost at work.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the probability of diseased state with and without morcellation are derived from a single source [45]. Additionally, when establishing utilities for health states, we relied on a single source with its own limitations: small sample size (n 5 13), a single interviewer, the use of a 30-year time trade-off, and lack of questions about prognosis and recurrence scenarios secondary to emotional concerns for the patient [24].…”
Section: Discussionmentioning
confidence: 99%
“…In total, we identified 20 studies that examined the prevalence of occult uterine cancers in patients with presumed benign disease. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In total, 12 studies were limited to patients with presumed uterine leiomyomas as the only surgical indication and were included in the primary results, [22][23][24][25][26][28][29][30][31][32][33]37 whereas the remainder included other gynecologic surgical indications in addition to uterine fibroids. [18][19][20][21]27,[34][35][36] Of the 12 studies limited to patients with presumed uterine leiomyomas, only 1 was a prospective observational study, 32 whereas all others were retrospective analyses of individual institutions [22][23][24][25][28]…”
Section: Incidence Of Occult Cancer In Presumed Fibroidsmentioning
confidence: 99%
“…16 Uterine sarcomas are usually diagnosed incidentally by postoperative histopathology. 17 Although no reliable method is currently available to preoperatively detect or differentiate between myoma and uterine sarcoma, 18,19 preoperative evaluation remains critical, especially for perimenopausal patients. Endometrial biopsy should be performed in patients with abnormal vaginal bleeding to detect early malignancies.…”
Section: Preoperative Evaluationmentioning
confidence: 99%